Retrospective comparative study on efficacy and safety of different surgical procedures for pelvic organ prolapse - Wang, Yuquan; Guo, Xuewang; Yang, Weina; Liu, Dong; Wang, Meng; Xu, Yanying (Scientific reports, 2025)
The aim of this retrospective study was to analyze the efficacy and safety of lateral abdominal wall suspension during surgery compared with traditional procedures in patients with pelvic organ prolapse without uterine preservation. Collect the data of patients with uterine and vaginal wall prolapse who underwent surgery from January 2022 to December 2023. All patients were divided into three groups according to different surgical procedures: Study Group (laparoscopic total hysterectomy + bilateral salpingectomy/oophorectomy + lateral abdominal wall suspension + posterior colporrhaphy), Control Group 1 (laparoscopic-assisted vaginal total hysterectomy + bilateral salpingectomy/bilateral oophorectomy + anterior and posterior colporrhaphy), and Control Group 2 (vaginal total hysterectomy + anterior and posterior colporrhaphy).Statistically analyze the clinical indicators and recurrence situations in different Groups. Patients in Study group exhibited significantly higher preoperative POP-Q staging for pelvic organ prolapse severity( P < 0.01), longer operative times( P = 0.01, P < 0.01), but significantly reduced intraoperative blood loss( P = 0.01, P < 0.01)and shorter postoperative urinary catheterization duration( P = 0.01, P < 0.01) compared to the other two groups. No differences were detected in postoperative infection, vaginal bleeding or duration of hospitalization( P > 0.05). However, stress incontinence in 1-year after operation has no difference between study group and control groups. Recurrence rates in Control Group 1 is higher than Study Group ( P = 0.02), While, it has no difference between Study Group and Control Group 2. Lateral abdominal wall suspension, despite a longer operative duration, surpasses traditional surgeries in minimizing intraoperative blood loss, cutting down the time of postoperative urinary catheter retention, and lowering the postoperative recurrence rate. To firmly establish the long-term curative effects and safety of lateral abdominal wall suspension, future research with larger sample sizes and longer follow-up periods is essential.